Factors that influence employee’s turnover intention at Puspakom Sdn. Bhd. / Nur Sarah Halip and Syamimi Afiqah Ismail - Halip, Nur Sarah; Ismail, Syamimi Afiqah (Faculty of Business and Management, 2014)
Workforce is a heavyweight component of any organization and therefore employees are always considered as the greatest asset of an organization. Without employees, organizations will not be able to produce business results, achieve organization goals, or meet its financial objectives. However, nowadays most of the organizations are facing the employee turnover problem and failure to retain their workforce. Besides that, there have been frequent complaints from employees of Puspakom Sdn. Bhd that they are dissatisfied with their job and management team which is lead to the turnover intention. In this research study, the influence factors that lead to the employees’ turnover intention at workplace are personal factors, pull factors and push factors. Moreover, data is collected by distributing questionnaire to 123 respondents from the organization by using probability sampling which is simple random sampling. Nevertheless, majority of the respondent age are between 26-30 years old with mostly in executive level of position The results indicate that all factors (personal, pull and organizational commitment) have contributed in the employee’s turnover intentions. However, organizational commitment has negative relationship with employees’ turnover intentions. This research study also said to be beneficial to the organization in order to understand their employees’ voice. It will help organization to retain their human resources and managing the human capital because employees are the main factors of the successfulness in any organization. Recommendations for future research are also been discussed.